نظرية الوكالة مشاكل وحلول - سليم, حنكة; الحبيب, تامة; البشير, جورني; محمد, معيطي (University of eloued جامعة الوادي, 2021)
"الملخص: تهدف هذه الدراسة إلى إلى أي مدى ساهمت حوكمة الشركات في إيجاد حلول ومشاكل نظرية الوكالة، حيث تمت معالجتها بالاعتماد على دراسة ميدانية بأسلوب الاستبيان وتكونت عينة الدراسة من 51 فرداً من أساتذة جامعيين ومهنين وممارسي مهنة المحاسبة في الجزائر. وخلصت الدراسة إلى أنه توجد فروق ذات دلالة إحصائية في تأثير دور حوكمة الشركات في الحد من مخاطر نظرية الوكالة على واقع نظرية الوكالة في الشركات ومساهمة الموظفين في رأس المال وربحية الشركات. ""Abstract: This study aims to the extent to which corporate governance contributed to find solutions and problems of agency theory, as it was addressed by relying on a field study using a questionnaire method. The study’s sample consisted of 51 university professors, professionals and accountancy practitioners in Algeria. The study concluded that there are statistically significant differences in the impact of the role of corporate governance in reducing agency theory risks on the reality of agency theory in companies and employees contribution to capital and corporate profitability. "
مذكرة ماستر محاسبة
Keywords: الوكال، نظرية; Agency Theory